Konsep Model Kepemimpinan Direktif dan Instruksional - Adnan; Shobri; Muslihah, Eneng (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to explain directive and instructional leadership. Literature study is used as a method in research. Data is taken, collected, and analyzed from books and scientific journals with similar topics, then used as writing and conclusions. Study results show that using directive and instructional leadership In a leadership model that is directive and instructional, a leader will provide direct guidance to his team members to achieve the goals achieved. This model is often used in situations where the task to be completed is very clear and requires quick decision-making. As well as exactly.